Antiarthritic effects of water extraction of Centella asiatica L. leaves on adjuvant-induced arthritis in rats - Hashim, Ridzwan; Md Radai, Wan Syahirah; Althunibat, Osama Yousef; Zulkipli, Farah Hanis (Academic Journals, 2013)

(untitled)
The antiarthritic effect of water extraction of C. asiatica leaves in the adjuvant-induced arthritis in rats was investigated. Prior to this, the chemical constituents in C. asiatica leaves were determined through phytochemical analysis and were found to contain alkaloids, terpenoid, flavonoid and tannin. Leaves of C. asiatica were subjected to water extraction by using blender, filtrated and then freeze-dried to produce dried powder. C. asiatica extracts (CAE) as well as the positive control, dexamethasone showed significant effects when applied to establish adjuvant arthritis. Foot volume of rats was measured by using water displacement method known as plethysmography. Intraperitoneal (i.p) administration of CAE for doses 30 mg/kg and 300 mg/kg b.w. reduced the arthritic edema in the ipsilateral paw of rats with maximal inhibition 54.19 ± 6.43% and 41.05 ± 3.41%, respectively. CAE (doses 30 and 300 mg/kg i.p) was able to prevent the spread of the edema from the ipsilateral to the contralateral paws, which indicated the systemic inhibition. Similar results were observed using steroidal anti-inflammatory agent, dexamethasone (1 mg/kg b.w. i.p). Thus, the findings suggests that the water extract of leaves C. asiatica exerted an antiarthritic activity.